Investigating the relationship between technology acceptance and e-Learning readiness among English as a Second Language (ESL) students at Politeknik Kota Bharu - Kamilah Zainuddin (2023)
A low level of acceptance during e-Learning will affect the English as a Second Language (ESL) student's performance and interest in continuing it in the future. To recognise the reasons for the low level of acceptance, we must initially identify what is the level of acceptance among the users. Thus, this study was intended to investigate the level of acceptance and the relationship that exists between technology acceptance and the level of readiness for e-Learning among ESL students in Politeknik Kota Bharu, via the use of Learning Management System (LMS) which is known as Curriculum Information Document Online System (CIDOS) version 3.5. Additionally, it sought to identify the individual differences in ESL students' technology acceptance to use e-Learning based on three demographic factors, namely gender, type of devices used, and the course of study. An online cross-sectional survey based on a simple random sampling received responses from 285 ESL students representing eight Diplomas in Engineering programs who enrolled in a Communicative English course at Politeknik Kota Bharu, Kelantan, Malaysia. Descriptive and inferential techniques were used in this correlational study to evaluate the data. According to the findings, English as a Second Language (ESL) students at Politeknik Kota Bharu had a high level of acceptance of technology in terms of its perceived usefulness, perceived ease of use, behavior intention, and attention to use e-Learning. Concerning the readiness constructs of psychology, human resource, equipment, technology, and content it should not come as a surprise that they were completely ready to implement e-Learning. In addition, it was shown that there was a strong correlation between the level of acceptance of technology among ESL students and their readiness for e-Learning. In addition, the results indicated that neither gender nor course of study significantly affected respondents' e-Learning technology acceptance except for the type of devices used. By providing a picture of the ESL students' technology acceptance and readiness in the adoption of e-Learning, this study could offer beneficial implications for the developers of e-Learning applications and for education providers to guide the design and implementation of comprehensive e-Learning systems.